Eslicarbazepine Acetate as Adjunctive Therapy for Refractory Partial-Onset Seizures in Adults: A Randomized, Double-Blind, Placebo-Controlled Trial - Qahir, Muhammad; Kakar, Amanullah; Abdulkhaliq,; Nasar, Abdul Bari; Ihsan ul Haq,; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Refractory partial-onset seizures present a significant therapeutic challenge, necessitating novel adjunctive treatments. This study aimed to evaluate the efficacy, safety, and tolerability of eslicarbazepine acetate (ESL) as an add-on therapy in adults with this condition. Methods: This was a single-center, randomized, double-blind, placebo-controlled, parallel-group trial conducted from January 2023 to December 2024. Eighty-nine adults with refractory partial-onset seizures (≥4 seizures/4 weeks despite 1–3 stable AEDs) were randomized 1:1:1 to placebo (n=30), ESL 800 mg (n=30), or ESL 1200 mg (n=29) once daily for 14 weeks after an 8-week baseline. The primary endpoint was the change in 4-week seizure frequency from baseline, analyzed using ANCOVA. Secondary endpoints included responder rates, seizure freedom, quality of life (QOLIE-31), depressive symptoms (MADRS), and adverse events. Results: Both ESL doses significantly reduced seizure frequency compared to placebo (p<0.001). LS mean change from baseline was −6.8 seizures/4 weeks (ESL 800 mg) and −8.3 seizures/4 weeks (ESL 1200 mg), versus −1.2 for placebo. Responder rates (≥50 reduction) were significantly higher with ESL (43.3% for 800 mg, 51.7% for 1200 mg) versus placebo (16.7%). Seizure freedom occurred in 10.0% (ESL 800 mg) and 13.8% (ESL 1200 mg) of patients. QOLIE-31 scores significantly improved (p<0.001), and MADRS scores decreased dose-dependently. Adverse event incidence was dose-dependent (placebo: 30.0%; ESL 800 mg: 53.3%; ESL 1200 mg: 65.5%), with common AEs including dizziness, somnolence, and diplopia. Hyponatremia occurred in 13.8% of the ESL 1200 mg group. Subgroup analysis showed superior efficacy for ESL 1200 mg in complex partial seizures and patients on two concomitant AEDs. Conclusion: ESL, at both 800 mg and 1200 mg once daily, is an effective and generally well-tolerated adjunctive therapy for adults with refractory partial-onset seizures, improving seizure control and patient-reported outcomes.